Multi-site desmoplastic small round cell tumors are genetically related and immune-cold - Chia-Chin Wu; Hannah C. Beird; Salah-Eddine Lamhamedi-Cherradi; Melinda Soeung; Davis Ingram; Danh D. Truong; Robert W. Porter; Sandhya Krishnan; Latasha Little; Curtis Gumbs; Jianhua Zhang; Mark Titus; et al. (npj Precision Oncology, 2022)
Abstract Desmoplastic small round cell tumor (DSRCT) is a highly aggressive soft tissue sarcoma that is characterized by the EWSR1-WT1 fusion protein. Patients present with hundreds of tumor implants in their abdominal cavity at various sites. To determine the genetic relatedness among these sites, exome and RNA sequencing were performed on 22 DSRCT specimens from 14 patients, four of whom had specimens from various tissue sites. Multi-site tumors from individual DSRCT patients had a shared origin and were highly related. Other than the EWSR1-WT1 fusion, very few secondary cancer gene mutations were shared among the sites. Among these, ARID1A, was recurrently mutated, which corroborates findings by others in DSRCT patients. Knocking out ARID1A in JN-DSRCT cells using CRISPR/CAS9 resulted in significantly lower cell proliferation and increased drug sensitivity. The transcriptome data were integrated using network analysis and drug target database information to identify potential therapeutic opportunities in EWSR1-WT1-associated pathways, such as PI3K and mTOR pathways. Treatment of JN-DSRCT cells with the PI3K inhibitor alpelisib and mTOR inhibitor temsirolimus reduced cell proliferation. In addition, the low mutation burden was associated with an immune-cold state in DSRCT. Together, these data reveal multiple genomic and immune features of DSRCT and suggest therapeutic opportunities in patients.